Repositioning Librarians Registration Council of Nigeria (LRCN) for Integration and Registration of Paraprofessionals - Kasa, Allahde Shehu & Mathias Gabriel (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
Librarians Registration Council of Nigeria (LRCN) has greatly increased the impetus of librarianship in Nigeria and among professionals, thereby making it a pride to behold. The profession is a communal one having only one value of trade to help harness, organize, secure, store and retrieve information when the need arises. This paper advocates the integration and registration of paraprofessionals by LRCN because they are major stakeholders in the delivery of library and information services and occupy the base and mid layers of the personnel pyramid of practicing librarians in Nigeria. The paper leveraged on recognised library cadres and educational qualifications to advocate for the inclusion of paraprofessionals by LRCN. Amending the law that established LRCN may resolve the challenge. When implemented it will be a win-win to LRCN and those certificated by its accredited institutions across Nigeria. LRCN will have its mission and vision actualized and members guaranteed benefits such as well-established career paths, recognition by their parent institutions and an arbiter when the need arises.